Kepemimpinan dan Kepercayaan (Trust) Terhadap Komitmen Organisasi Pada Guru Bimbingan dan Konseling di SMP - Hegar Harini (Universitas Mathla'ul Anwar Banten, 2018)
LEADERSHIP AND TRUST ON THE ORGANIZATIONAL COMMITMENT ON THE SCHOOL COUNSELORS OF JUNIOR HIGH SCHOOL. The objective of this research is aimed at obtaining the information that related to the effects of leadership, trust and the organizational commitment, of the teacher of junior high school in Pasar Minggu District, South of Jakarta. The method used ia a survey by structured interview with a sample of 22 school counselors of junior high school in Pasar Minggu District, South of Jakarta. The data collected were processed by path analysis. The result proved that the trust was directly affected by leadership. There are direct effects of the leadership on organizational commitment and there are direct effects of the trust on organizational commitment. However, there is an indirect effect of leadership on organizational commitment through trust. The result can be concluded that two factors should be considered in the improvement of the organizational commitment.